AMAP report to the meeting of Senior Arctic Officials, Kautokeino, November 19-20, 2008. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2008)
Arctic Council working group Arctic Monitoring and Assessment Programme (AMAP)s report to SAOs from the Arctic Council's Senior Arctic Officials meeting in Kautokeino, Norway, November 19-20 2008.